Russians’ Participation in Charitable Donations: Factors and Degree of Involvement - МерсияноваИрина Владимировна (Journal of Economic Sociology, 2010)
There is a lot of evidence that preconditions for development philanthropic institutions have been created in Russia within the last decade. Still there are only few papers devoted to the analysis of Russians’ charitable activity. The lack in empirical data presents a major obstacle for this kind of research. This article is aimed to fill a gap in the empirical knowledge and demonstrate an actual degree of Russians’ involvement in donations. Main factors affecting charitable activities are described. The nationwide Russian empirical data set is viewed through the prism of international context of philanthropic activity. The empirical data was collected by Centre for Studies of Civil Society and Non-for-profit Sector (CSCSNS) in the frameworks of the Monitoring of the development of Russian civil society. The project is supported by the Program for Fundamental Studies of the State University ― Higher School of Economics.